Algebraic functions in quasiprimal algebras - Campercholi, Miguel Alejandro Carlos (2014)
A function is algebraic on an algebra math formula if it can be implicitly defined by a system of equations on math formula. In this note we give a semantic characterization for algebraic functions on quasiprimal algebras. This characterization is applied to obtain necessary and sufficient conditions for a quasiprimal algebra math formula to have every one of its algebraic functions be a term function. We also apply our results to particular algebras such as finite fields and monadic algebras.